ON SIX SPECIES OF MONOGENETIC TREMATODES, PARASITIC ON THE GILLS OF MARINE FISHES FROM THE INDIAN SEAS - R VISWANATHAN UNUNNITHA (BRIN Publishing (Penerbit BRIN), 1968)
Six species of monogenetic trematodes, collected from the gills of marine fishes of the south west coast of India, are described. Two new genera, Churavera and Eyelavera have been created to accommodate the two new species Churavera macrova andÂ Eyelavera typica. Of the remaining four species which all come under the more familiar genera Gastrocotyle and Pseudaxine, three viz., Gastrocotule kalla., Gastrocotyle kurra and Pseudaxine kurra are new species while Gastrococule indica SUBHAPRADHA,1951, is recorded for the first time from the west coast of India.